2019
DOI: 10.1609/aaai.v33i01.33011435
|View full text |Cite
|
Sign up to set email alerts
|

A SAT+CAS Approach to Finding Good Matrices: New Examples and Counterexamples

Abstract: We enumerate all circulant good matrices with odd orders divisible by 3 up to order 70. As a consequence of this we find a previously overlooked set of good matrices of order 27 and a new set of good matrices of order 57. We also find that circulant good matrices do not exist in the orders 51, 63, and 69, thereby finding three new counterexamples to the conjecture that such matrices exist in all odd orders. Additionally, we prove a new relationship between the entries of good matrices and exploit this relation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The concept of a programmatic SAT solver was first introduced by Ganesh et al (2012) where a programmatic SAT solver was shown to be more efficient than a standard SAT solver when solving instances derived from RNA folding problems. More recently, a programmatic SAT solver was also shown to be useful when searching for Williamson matrices and good matrices by Bright et al (2018aBright et al ( , 2019. Generally, programmatic SAT solvers perform well when there is additional domain-specific knowledge known about the problem being solved.…”
Section: Stage 2: Construct the Second Sequence B From Amentioning
confidence: 99%
“…The concept of a programmatic SAT solver was first introduced by Ganesh et al (2012) where a programmatic SAT solver was shown to be more efficient than a standard SAT solver when solving instances derived from RNA folding problems. More recently, a programmatic SAT solver was also shown to be useful when searching for Williamson matrices and good matrices by Bright et al (2018aBright et al ( , 2019. Generally, programmatic SAT solvers perform well when there is additional domain-specific knowledge known about the problem being solved.…”
Section: Stage 2: Construct the Second Sequence B From Amentioning
confidence: 99%
“…Our focus was applying the SAT+CAS paradigm to the Williamson conjecture from combinatorial design theory, but we believe the SAT+CAS paradigm shows promise to be applicable to many other problems and conjectures. In fact, the SAT+CAS paradigm has recently been used to enumerate complex Golay pairs (Bright et al, 2018b) and good matrices (Bright et al, 2019). However, the SAT+CAS paradigm is not something that can be effortlessly applied to problems or expected to be effective on all types of problems.…”
Section: Conclusion and Advicementioning
confidence: 99%
“…Additionally, the entries of best matrices can be shown to satisfy certain constraints similar to constraints that Williamson matrices [74], good matrices [9], and the coefficients of complex Golay pairs [15] satisfy. In the appendix we show that the entries of best matrices satisfy the relationship a k b k c k d k a 2k b 2k c 2k = −1 for k = 0 with indices reduced mod n. Because of the anti-symmetry of A, B, and C, when k = n/3 the product constraint reduces to d k = 1 and in this case can be encoded as a unit clause.…”
Section: Conquer Phasementioning
confidence: 99%
“…We used MathCheck to show that certain graph theoretic conjectures held up to bounds that had not previously been verified [79]. Later we applied MathCheck to find (and disprove the existence of in certain orders) Williamson matrices [12], complex Golay pairs [14], and good matrices [9].…”
Section: The Sat+cas Paradigmmentioning
confidence: 99%